Enhancing the phase stability of TiNi intermetallic compound via nanocrystallization in an irradiated multicomponent vanadium alloy. (January 2022) - Wu, Z.F.; Liang, Y.X.; Tang, J.J.; Wang, Y.F.; Zhang, S.L.; Meng, Q.N.; Yan, Y.; Xu, C.; Wang, J.; Shen, T.D.; Qiao, Y.Q.; Fu, E.G.
Graphical abstract: Highlights: Micron-scale TiNi matrix with inside nano-scale VCr precipitates became amorphous while micron-scale VCr matrix including nano-scale TiNi precipitates exhibited a high structural stability in V34 Ti25 Cr10 Ni30 Pd1 alloy after radiation. The radiation tolerance of TiNi intermetallic compound in V34 Ti25 Cr10 Ni30 Pd1 alloy was increased after nanocrystallization upon irradiation. VCr solid solution phase exhibits a better radiation tolerance than TiNi intermetallic phase. Abstract: Intermetallic compounds often have a low radiation tolerance due to the low recombination rate of radiation-induced defects. In the present work, we designed a novel multicomponent vanadium-based alloy (MVA), V34 Ti25 Cr10 Ni30 Pd1, containing a micron-scale TiNi matrix phase with VCr nanoprecipitates (NPs) and a micron-scale VCr matrix phase with TiNi NPs. The MVA was irradiated with 6 MeV Ti 3 + ions with a radiation dose of 5 × 10 15 i o n s / c m 2 at room temperature. Results indicated that the micron-scale intermetallic TiNi matrix along with VCr NPs inside both became amorphous, while the micron-scale VCr matrix including numerous intermetallic TiNi NPs both exhibited a high structural stability after ion irradiation. The intermetallic TiNi matrix becomes amorphous due to the accumulation of radiation-induced defects, and the intermetallic TiNi NPs in VCr matrix have a high stability of crystallographic structure due to high-density interfaces between NPs and matrix. These results indicate that the phase stability of TiNi intermetallic compound is increased after nanocrystallization. Besides, the discrepancy of two matrix phases including precipitates after ion irradiation, and the underlying mechanisms are discussed in detail in this work. This work gives a guidance for designing new vanadium alloys and intermetallic compounds with enhanced structural stability under ion irradiation.